Evaluating attitudes, behaviors, and relevant factors in dispensing antibiotics without prescription by pharmacies: a cross-sectional study in Vietnam - Hung, P. N.; Phu, H. L.; Huong, V. T. M.; Phuong, T. N.; Tuong, V. L.; Tram, H. N.; Vinh, Q. D.; Minh, N. L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Objectives. To standardize a questionnaire about drug dispensers’ attitudes and behaviors in dispensing antibiotics without prescription, and to evaluate drug dispensers’ attitudes, behaviors, and relevant factors in dispensing antibiotics without prescription at community pharmacies in Can Tho City, Vietnam. Methods. A descriptive cross-sectional study was conducted among community pharmacists in Can Tho City, Vietnam from June to December 2022. A self-administered questionnaire designed according to the Theory of Planned Behavior was used for data collection. The questionnaire was composed of 33 statements scored on the 5-point Likert scale, which was completed by interviews with 180 pharmacy dispensers to Can Tho. Exploratory Factor Analysis was also utilized to uncover major determinants of dispensing antibiotics without prescription. Results. Of the 180 participants, 65% of drug dispensers were female (n=117), 59.4% were university graduates (n= 107), and 80.6% had experience of less than 10 years (n=145). A pharmacy is the first destination people think about when they have a health issue. Unfortunately, dispensing antibiotics without a valid prescription is not in compliance with governmental regulations. In the study, perceived behavioral control factors were found to be the most critical determinants of the behavior, followed by subjective norms. By contrast, attitudinal factors presented no impact on intention to dispensing antibiotics without prescription.Conclusions. The provision of non-prescription is primarily influenced by the perception of the distributors and external factors. Developing interventions is necessary to increase public awareness of the misuse and misunderstanding of antibiotics.